2005
DOI: 10.1002/ppap.200400077
|View full text |Cite
|
Sign up to set email alerts
|

Water Treatment Using Discharge on the Surface of a Bubble in Water

Abstract: Summary: A new method for water treatment utilizing radicals produced by a discharge on the surface of a bubble in water is proposed and this method is applied to the de‐color of indigo solution whose original color is blue. The discharge of this method begins at the crossing points of mesh electrode, acrylic resin spacer, and bubbling gas (i.e., called a triple junction where there is a weak point for the electrical breakdown in the electrical power devices). This weak point for the electrical breakdown is us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 12 publications
3
41
0
Order By: Relevance
“…We reported that H 2 O 2 was generated in the distilled water irradiated with the plasma jet and that the H 2 O 2 concentration increased with irradiation time according to results of flow injection analysis * Corresponding author: kuwahata@keyaki.cc.u-tokai.ac.jp (FIA) [19]. Some reports show that, similar to our results, the generation of H 2 O 2 in water was induced by on-water discharge [20,21] and on-water irradiation of atmospheric-pressure plasma [22,23].…”
Section: Introductionsupporting
confidence: 79%
“…We reported that H 2 O 2 was generated in the distilled water irradiated with the plasma jet and that the H 2 O 2 concentration increased with irradiation time according to results of flow injection analysis * Corresponding author: kuwahata@keyaki.cc.u-tokai.ac.jp (FIA) [19]. Some reports show that, similar to our results, the generation of H 2 O 2 in water was induced by on-water discharge [20,21] and on-water irradiation of atmospheric-pressure plasma [22,23].…”
Section: Introductionsupporting
confidence: 79%
“…Bruggeman showed 1 Author to whom any correspondence should be addressed. that streamers preferably take paths along the surface of the bubble when the bubble is immersed in a high dielectric constant liquid such as water [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Electric discharges in liquids, and streamers in particular, are being intensively investigated due to their wide-ranging applications, from removal of volatile organic compounds (VOCs) from water to surgical instruments [1][2][3][4][5]. In most cases, streamers do not propagate directly through the liquid phase.…”
Section: Introductionmentioning
confidence: 99%
“…Th e discharge of this method has been thought to begin at the crossing points of mesh electrode, acrylic resin spacer, and bubbling gas (i.e., called a triple junction, where there is a weak point for the electrical breakdown in the electrical power devices). Th is weak point for the electrical breakdown has been very actively used for the surface discharge [46].…”
Section: Application Of Plasma For Water Purifi Cationmentioning
confidence: 99%